Demonstration: A cloud-control system equipped with intrusion detection and mitigation - Akbarian, Fatemeh; Tärneberg, William; Fitzgerald, Emma; Kihl, Maria (Electronic Communications of the EASST, 2021)
The cloud control systems (CCs) are inseparable parts of industry 4.0. The cloud, by providing storage and computing resources, allows the controllers to evaluate complex problems that are too computationally demanding to perform locally. However, connecting physical systems to the cloud through the network can provide an entry point for attackers to infiltrate the system and cause damage with potentially catastrophic consequences. Hence, in this paper, we present a demo of our proposed security framework for CCs and demonstrate how it can detect attacks on this system quickly and mitigate them.